On the Stator Slot Geometry of a Cable Wound Generator for Hydrokinetic Energy Conversion - Mårten Grabbe; Sandra Eriksson; Mats Leijon (The Scientific World Journal)
The stator slot geometry of a cable wound permanent magnet synchronous generator for hydrokinetic energy conversion is evaluated. Practical experience from winding two cable wound generators is used to propose optimized dimensions of different parts in the stator slot geometry. A thorough investigation is performed through simulations of how small geometrical changes alter the generator performance. The finite element method (FEM) is used to model the generator and the simulations show that small changes in the geometry can have large effect on the performance of the generator. Furthermore, it is concluded that the load angle is especially sensitive to small geometrical changes. A new generator design is proposed which shows improved efficiency, reduced weight, and a possibility to decrease the expensive permanent magnet material by almost one-fifth.